Sequencing of Treponema pallidum subsp. pallidum from isolate UZ1974 using Anti-Treponemal Antibodies Enrichment: First complete whole genome sequence obtained directly from human clinical material - Grillová, Linda; Giacani, Lorenzo; Mikalová, Lenka; Strouhal, Michal; Strnadel, Radim; Marra, Christina; Centurion-Lara, Arturo; Poveda, Lucy; Russo, Giancarlo; Čejková, Darina; Vašků, Vladimír; Oppelt, Jan; et al. (PloS one, 2018)
Treponema pallidum subsp. pallidum (TPA) is the infectious agent of syphilis, a disease that infects more than 5 million people annually. Since TPA is an uncultivable bacterium, most of the information on TPA genetics comes from genome sequencing and molecular typing studies. This study presents the first complete TPA genome (without sequencing gaps) of clinical isolate (UZ1974), which was obtained directly from clinical material, without multiplication in rabbits. Whole genome sequencing was performed using a newly developed Anti-Treponemal Antibody Enrichment technique combined with previously reported Pooled Segment Genome Sequencing. We identified the UW074B genome, isolated from a sample previously propagated in rabbits, to be the closest relative of the UZ1974 genome and calculated the TPA mutation rate as 2.8 x 10(-10) per site per generation.
Keywords: genom bakteriální; Mutation Rate; Humans; syfilis; Phylogeny; Sequence Analysis, DNA; mutační rychlost; Whole Genome Sequencing; lidé; zvířata; genetická variace; sekvenování celého genomu; sekvenční analýza DNA; Genetic Variation; fylogeneze; Syphilis; králíci; Animals; Treponema pallidum; Genome, Bacterial; Rabbits